Dynamics of Civil Islam in Identity Politics of Indonesia and Malaysia - Mikail, Kiki; Ibrahimian, Hojjatollah; Idi, Abdullah; Hadi, Abdul (UIN Sunan Gunung Djati Bandung, 2023)
This study explores the role of Civil Islam within the context of identity politics in Indonesia and Malaysia, focusing on its impact on the democratization process and public policy formulation in both countries. Utilizing a qualitative approach, the research gathers data from primary and secondary sources to analyze how Civil Islam, through its interactions with the state and society, influences and is shaped by local political dynamics. The findings indicate that Civil Islam in Indonesia and Malaysia plays a crucial role in strengthening democracy through active participation in identity politics, directly responding to socio-political challenges emerging in the post-reform era. In Indonesia, the movement contributes to the consolidation of Pancasila as the foundational national ideology, while in Malaysia, it strives to harmonize ethnic and religious differences within a constitutional democracy framework. This study enriches our understanding of Islamic social movements not only as responses to social injustices but also as significant actors in the formulation and implementation of inclusive national ideologies. The findings have important implications for policymakers and social activists in designing strategies that promote social integration and political stability in culturally diverse regions.